Will Internet Market Newness Improve Performance? An Empirical Study on the Internet Market Innovation of Offline Retailers in China - Cheng Lu (MDPI AG, 2021)
With the increasing impact of the Internet, the transformation of traditional retailers through Internet innovation has become a pressing issue. Based on the theory of innovation and marketing capability, this study investigated the relationships among adaptive marketing capability (AMC), Internet market newness, and innovation performance. The mediation effect of compromise on these relationships was also investigated. Through data analysis of 205 questionnaires in China, the current study confirmed that interaction between AMC and Internet market newness significantly affected innovation performance, and Internet market newness positively affected performance only when AMC was high. The results also demonstrated that compromise mediated the interaction with performance. AMC moderated not only the direct effects on performance by Internet market newness, but the effects on compromise by Internet market newness.